Teaching reconceptualized family resemblance approach to nature of science in lower secondary classroom - Çilekrenkli, Ayşegül. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Erduran and Dagher’s (2014) Reconceptualized Family Resemblance Approach to Nature of Science (RFN) is a relatively new approach in teaching nature of science (NOS). The purpose of this study is to investigate the effectiveness of RFN approach on 5th grade students’ understanding and perceptions of NOS. With an experimental, convergent parallel mixed method study design the change in students’ understanding and perceptions of NOS is explored. Participants of the study are 64 female, 5th grade students and their science teacher. Intervention is conducted with RFN based instruction or regular practice in experimental and control groups, respectively. The quantitative data source is adapted from the RFN Questionnaire (Kaya, Erduran, Aksoz & Akgun, 2018). Qualitative data is gathered through semi-structured student interviews before and after the intervention. RFN Student Questionnaire was administered as pre, post and delayed post-test. T-test indicated that groups were initially homogeneous in their total and category-based scores except for the scientific practices category. Mixed ANOVA showed that there was a significant main effect of the teaching method. Pairwise comparisons revealed that the mean changes from the pretest to post-test were significant for the total test scores and methods and methodological rules of science, scientific knowledge, and social institutional categories. Therefore, among the category-based scores, experimental students significantly outperformed their peers except for the aims and values of science and scientific practices categories. Analysis of student interviews with thematic coding and constant comparison of the codes also supported these results. Overall, the study has implications for the integration of a holistic account of nature of science to secondary school science education content.
Keywords: Science -- Study and teaching (Secondary)